2022
DOI: 10.1021/acs.energyfuels.2c00551
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Supported Interpenetrating Polymer Network Flexible Solid Electrolytes for Lithium-Ion Batteries

Abstract: In this report, we have prepared the imidazoliumbased ionic liquid-incorporated interpenetrating polymer network (IPN) electrolyte membrane containing cellulose triacetate with polyethylene glycol dimethyl acrylate and polyethylene oxide by the UV-induced polymerization method. A facile IPN electrolyte membrane appears to be homogeneous in nature with high mechanical strength, excellent thermal stability, and exhibits optimum ionic conductivity of the order of 2.84 × 10 −3 S cm −1 . The oxidative stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…From the Figure 9a, it can be seen that the ionic conductivity increased continuously with increasing LiTFSI from 5 to 30 wt%, which the ionic conductivity increased with LiTFSI increased and then the ionic conductivity decreased continuously. The main reason for the large conductivity at the initial stage with increasing lithium salt concentration is that as the LiTFSI content increase, the LiTFSI continue to dissociate to form free mobile carriers, and the ionic conductivity continue to increase 7,12 . We found that the LiTFSI addition is optimal at about 30%, and its ionic conductivity is 3.1 × 10 −5 S cm −1 at 30°C.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…From the Figure 9a, it can be seen that the ionic conductivity increased continuously with increasing LiTFSI from 5 to 30 wt%, which the ionic conductivity increased with LiTFSI increased and then the ionic conductivity decreased continuously. The main reason for the large conductivity at the initial stage with increasing lithium salt concentration is that as the LiTFSI content increase, the LiTFSI continue to dissociate to form free mobile carriers, and the ionic conductivity continue to increase 7,12 . We found that the LiTFSI addition is optimal at about 30%, and its ionic conductivity is 3.1 × 10 −5 S cm −1 at 30°C.…”
Section: Resultsmentioning
confidence: 76%
“…The main reason for the large conductivity at the initial stage with increasing lithium salt concentration is that as the LiTFSI content increase, the LiTFSI continue to dissociate to form free mobile carriers, and the ionic conductivity continue to increase. 7,12 We found that the LiTFSI addition is optimal at about 30%, and its ionic conductivity is 3.1 Â 10 À5 S cm À1 at 30 C. Then as the LiTFSI content continue to increase, the ionic conductivity will start to decrease significantly. The main reasons for the decline: first, a large number of high concentrations of LiTFSI in the polymer system is not "dissolved" but in the form of ion pairs, which do not play a role in ion transport; second, the high concentration of LiTFSI lead to excessive aggregation of ions to form ion clusters, further reduce the effective charge number and ion mobility.…”
Section: Ionic Conductivity and Electrochemical Stability Windowmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, when the added plasticizers or liquid electrolytes were ionic materials (e. g. ionic liquids (ILs)), the ions of such materials could also interact with the polysaccharides. On one hand, the interactions between ILs and polysaccharides could inhibit the crystallization of polysaccharides and reduce their crystallinity, thus increasing the ionic conductivity of polysaccharides [59,125,127,128] . The strong intermolecular interactions between the plasticizers such as glycerol and polysaccharides have the similar enhancement effect [129–131] .…”
Section: Application Of Natural Polysaccharides In Polymer Electrolytesmentioning
confidence: 99%
“…Several attempts have been made to obtain amorphous polyether matrices with adequate mechanical properties to facilitate their use in practical applications. For instance, researchers have used materials such as plasticizers [ 19 , 20 ], organic fillers [ 21 , 22 , 23 ], comb polymers [ 24 , 25 ], and interpenetrating polymer networks (IPNs) [ 26 , 27 , 28 , 29 ] as well as methods such as copolymerization [ 30 , 31 ] and cross-linking [ 32 , 33 , 34 ] to reduce the glass transition temperature and crystallinity of polymers. Cross-linked polymer networks effectively improve the mechanical properties and stability of SPEs.…”
Section: Introductionmentioning
confidence: 99%